Exploring the relationships between macrophyte groups and environmental conditions in lake ecosystems - Monika Różańska-Boczula; Joanna Sender (Scientific Reports)
Abstract This study presents research on the possibility of using lake macrophytes to create diagnostic and classification tools for trophically and morphologically diverse lakes. The diagnostic role of macrophytes was determined on the basis of the spatial and functional interrelationships of the various macrophyte groups, which include emergent, submerged, and floating species. In addition, an effort was made to reveal the morphometric features of the lakes that significantly affect the development of the distinguished macrophyte groups. The research was carried out comprehensively in the lakes of the Łęczna-Włodawa Lake District, a unique natural area due to the richness of hydrogenic areas. The lakes in the area are undergoing constant and rapid changes (despite the introduction of various forms of protection), which is reflected in the decreasing number of lakes and their eutrophication. Moreover, stoneworts, which are indicators of clean water, are disappearing from the lakes. The presence of specific groups of macrophytes led to the classification of these lakes as ecologically stable, meaning they are resistant to change and sustainable over time. The depth and surface area of the lakes were identified as the key morphometric features that most significantly influence the growth of macrophytes in eutrophic lakes, which were the most abundant in the study area. By analysing the consistent characteristics of macrophytes and lakes, four distinct classes were identified: emergent macrophyte dominated lakes, submerged macrophyte dominated lakes, low macrophyte density lakes, high macrophyte density lakes. The proposed classification can serve as a diagnostic framework for lakes, helping to identify them and improve our understanding of the changes occurring within these ecosystems.